2019
DOI: 10.1186/s12348-019-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 inhibition in the management of non-infectious uveitis and beyond

Abstract: Background Uveitis consists of a spectrum of inflammatory disorders characterized by ocular inflammation. The underlying pathophysiology consists of a complex interplay of various inflammatory pathways. Interleukin 6 is an important mediator of inflammation in uveitis and constitutes focus of research toward development of newer biological therapies in the management of non-infectious uveitis. Main body Pan-blockade of the inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 102 publications
(122 reference statements)
1
41
0
3
Order By: Relevance
“…Recently it was shown that in AVS-patients who underwent AVR had lower levels of plasma IL-6 after surgery, indicating that neutralizing IL-6 may be beneficial for attenuation of AVS [69]. Monoclonal humanized mouse antibody inhibitor of IL-6 receptor (Tocilizumab; Actemra, Roche AG, Basel, Switserland) antagonizes IL-6 signaling by preventing IL-6 binding with its corresponding receptors which is currently approved to treat rheumatoid arthritis [70]. In vascular smooth muscle cells it was shown that in vitro neutralization of IL-6 using anti-IL-6 antibodies reduced BMP2 and RUNX2 expression leading to decreased calcification [71].…”
Section: Future Perspectivementioning
confidence: 99%
“…Recently it was shown that in AVS-patients who underwent AVR had lower levels of plasma IL-6 after surgery, indicating that neutralizing IL-6 may be beneficial for attenuation of AVS [69]. Monoclonal humanized mouse antibody inhibitor of IL-6 receptor (Tocilizumab; Actemra, Roche AG, Basel, Switserland) antagonizes IL-6 signaling by preventing IL-6 binding with its corresponding receptors which is currently approved to treat rheumatoid arthritis [70]. In vascular smooth muscle cells it was shown that in vitro neutralization of IL-6 using anti-IL-6 antibodies reduced BMP2 and RUNX2 expression leading to decreased calcification [71].…”
Section: Future Perspectivementioning
confidence: 99%
“… 15 More recent studies noted efficacy of anti-IL-6R therapy in chronic cystoid macular edema secondary to other etiologies. 16 , 17 , 18 In a multicenter study of patients with refractory and noninfectious uveitic CME, treatment with TCZ showed a statistically significant reduction in macular thickness (432.7 ± 161.8 μm vs 259.1 ± 49.5 μm; p < 0.0001). Moreover, 21 of 23 eyes (91%) showed reduction in number of anterior chamber cells after 12 months of TCZ therapy, and resolution of vitritis was observed in 19 of 27 eyes (70.3%).…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated that ME could develop in up to 39% of patients on active mycophenolate treatment and that mycophenolate alone is not always sufficient in treating or preventing UME. 34 Additional immunomodulatory therapeutic agents, including anti-IL-6 tocilizumab, have been studied, 15 , 16 , 17 , 18 but these reports have been limited to cases of cystoid macular edema that occurred outside the context of post-cataract surgery. To the best of our knowledge, this is the first published case of a patient with refractory CME concerning for Irvine-Gass syndrome treated with anti-IL-6 therapy using tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations